2011
DOI: 10.1038/eye.2011.305
|View full text |Cite
|
Sign up to set email alerts
|

The island of ischaemia: submacular choroidal nonperfusion in giant cell arteritis

Abstract: We suggest that some unknown feature(s) of responders with high IOP enables steroids to reduce retinal edema. Conflict of interestThe authors declare no conflict of interest. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Nemiroff et al [24] noted that swept source OCT-A did provide a simple noninvasive tool to evaluate choroidal ischemia in 3 cases with GCA. While choroidal ischemia is often asymptomatic, ensuing visual loss have been reported when involving the macula or the papillomacular bundle [25][26][27][28][29]. Despite the fact that choroidal ischemia is described as being rare in the present literature [18,[25][26][27][28][29], it is probable that this irregularity of the choroidal circulation is frequently overlooked.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Nemiroff et al [24] noted that swept source OCT-A did provide a simple noninvasive tool to evaluate choroidal ischemia in 3 cases with GCA. While choroidal ischemia is often asymptomatic, ensuing visual loss have been reported when involving the macula or the papillomacular bundle [25][26][27][28][29]. Despite the fact that choroidal ischemia is described as being rare in the present literature [18,[25][26][27][28][29], it is probable that this irregularity of the choroidal circulation is frequently overlooked.…”
Section: Discussionmentioning
confidence: 70%
“…While choroidal ischemia is often asymptomatic, ensuing visual loss have been reported when involving the macula or the papillomacular bundle [25][26][27][28][29]. Despite the fact that choroidal ischemia is described as being rare in the present literature [18,[25][26][27][28][29], it is probable that this irregularity of the choroidal circulation is frequently overlooked. The current research and other communications [30,31] confirm that choroidal ischemia is frequently seen.…”
Section: Discussionmentioning
confidence: 70%
“…Gandhi confirmed that GCA can cause localized ischemic patches in the choroid while sparing the optic nerve and retinal arteries and recommended to consider the disease in inexplicable visual loss of older patients [45]. More recently, Ness et al reported a 64-year-old man who was referred with bilateral painless visual loss in whom they noticed placoid maculopathy related to choroidal hypoperfusion.…”
Section: Large Vessel Vasculitis (Lvv)mentioning
confidence: 98%
“…In 1 case, fluorescein angiography revealed focal perfusion defects in the submacular choroid, with sparing of the optic nerve and retinal arteries. 103 A recent retrospective review of 22 Mexican patients with GCA reported a mean (SD) age of 73 (7.9) years. The most frequent presenting symptoms included headache (90%), constitutional symptoms (86%), and polymyalgia rheumatica (59%).…”
Section: Giant Cell Arteritismentioning
confidence: 99%